The Impact of Individual Factors on Job Satisfaction and Organizational Loyalty among Secondary School Teachers in Baghdad - Jumaah, Zinah Hashim; Sejzi, Abbas Abdoli (Indian Journal of Information Sources and Services, 2025)
This study investigates the impact of individual factors—specifically personality traits, work-life balance, and occupational stress—on job satisfaction and organizational loyalty among secondary school teachers in Baghdad. Using a quantitative, correlational research design, data were collected from 385 randomly selected teachers through validated questionnaires measuring the Big Five personality traits, work-life balance, job satisfaction, occupational stress, and organizational loyalty. Analysis revealed that conscientiousness and job satisfaction are positively correlated, alongside work-life balance, while occupational stress negatively affected job satisfaction. Moreover, job satisfaction emerged as a strong predictor of organizational loyalty. Multiple regression analysis showed that personality traits, work-life balance, and occupational stress had a combined impact of 45% on occupational satisfaction, and that satisfaction was 40% of the variance in organizational commitment. The results indicate that fostering better work-life balance and lowering stress can improve the job satisfaction and organizational commitment of teachers who, as seen in many facets of life, are chronically over-committed to their roles. These outcomes are evident through policy and practice across the education system. Further research should focus on the role of emotional intelligence and support from leadership in employing these strategies.